Sunyaragi Cave as a Cultural Heritage Tourist Attraction of the People of Cirebon - Nurkhaeriyah, Nurkhaeriyah; Bastoni, Bastoni; Prawira Triutama, Oqke; Khairune Nisa, An Nuur (Ann Publisher, 2024)
This paper discusses how the process of changing Sunyaragi Cave from its initial function as a learning studio for the King's family to a place of deliberations on war strategies against Dutch colonialists to become a tourism industry at this time. This research uses a qualitative method approach to describe the natural condition of objects, where the researcher is the key instrument. The reason researchers choose descriptive research is to be able to describe systematically and accurately facts and characteristics about the population or a particular field. The researcher here intends to provide an overview of a particular social phenomenon that already exists. The discussion in this paper covers the history of Sunyaragi Cave, starting from its establishment and several restorations to its current condition. There is a cave management crisis until an agreement is reached by the responsible manager at this time and discusses how to change its function into a tourism industry and the uniqueness of cave architecture so that it has the potential to become a tourist destination for the cultural heritage of the people of Cirebon.